Abnormal Cranial Shape Preceding Radiographic Evidence of Craniosynostosis - Josie Z. Fazzino, BA; Esperanza Mantilla-Rivas, MD; Joseph H. Talbet, BA; Elina Kapoor, BA; Monica Manrique, MD; Jennifer L. McGrath, MD; Suresh N. Magge, MD; Albert K. Oh, MD; Gary F. Rogers, MD, JD, LLM, MBA, MPH (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary:. Premature fusion of a cranial suture is known to result in characteristic changes in the head shape, even when the synostosis involves only part of the suture. We report an unusual case of a patient seen at the age of 2 months for an abnormal head shape that was present at birth. The phenotype was consistent with an isolated fusion of the frontosphenoidal suture, but the suture was open on a high-resolution computed tomography scan finding. There was no improvement in cranial form after 6 months of helmet therapy, and a follow-up computed tomography scan image taken at age 10 months showed the development of bilateral isolated frontosphenoidal synostosis. This case highlights that an abnormal head shape may, in some patients, predate radiographic evidence of craniosynostosis.